#
Find the quadrant equation and not quadrant equation

2x²-6=3x

2(3x+1)²+0

5=(4x+1)²+6

7(2x²-1)=5x

2(3x+5)=x²

1
by bjginggoy

Log in to add a comment

2x²-6=3x

2(3x+1)²+0

5=(4x+1)²+6

7(2x²-1)=5x

2(3x+5)=x²

by bjginggoy

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

I think you mean 'quadratic' equation:

A quadratic equation is shown as:

ax²+bx+c=0 where a is not equal to 0.

Therefore none of them are quadratic equations.

A quadratic equation is shown as:

ax²+bx+c=0 where a is not equal to 0.

Therefore none of them are quadratic equations.